STUDY OF GREAT EROSIONS: A PROPOSAL OF METHODOLOGY - Raifran Abidimar de Castro; Luiz Carlos Araújo dos Santos (Sociedade & Natureza)
The erosions, are urban or agricultural they, have much time worry the urban and agricultural population, the public power and the particular companies. This concern has stimulated the studies on this partner-ambient problem. Guodie (1990 apud Guerra e Mendonça,.2004, p.228) “they affirm that the erosion of ground is the main and more serious impact caused for the action human being on the environment. Impacts these that can enclose since the loss of patrimony until problems of ambient degradation and losses of lives human beings.”Guerra & Cunha (2003, p.337), they affirm that: "In the reality, so that the problem can be understood of global form, integrated, holistic, it must be taken in account the existing relations between the ambient degradation and the causing society from that, at the same time, it suffers the effect and it looks for to decide, it recoups and it reconstitutes the degraded areas". Therefore one of the urban problems that more contribute for the growth of erosionsis the occupation of inadequate areas.As it is known first attitude that must be had for a necessary study of erosions is to analyze the erosive processes that act in the same one. On this subject, Guerra & Mendonça (2004, p. 229) they affirm that: "Some factors are the ones that intervene on the erosive processes: kinetic energy of the water of rains, chemical and physical properties of ground, forms and declivity of the hillsides, vegetal covering and handling of the ground ".